Factors Influencing Oxidative Imbalance in Pulmonary Fibrosis: An Immunohistochemical Study. (9th May 2011) - Inghilleri, Simona; Morbini, Patrizia; Campo, Ilaria; Zorzetto, Michele; Oggionni, Tiberio; Pozzi, Ernesto; Luisetti, Maurizio
Abstract : Background . Idiopathic Pulmonary Fibrosis (IPF) is a fatal lung disease of unknown etiology characterized by interstitial fibrosis determining irreversible distortion of pulmonary architecture. Reactive oxygen species (ROS) and markers of oxidative stress play a pivotal role in human IPF pathology, possibly through induction of epithelial-mesenchymal transition (EMT). Methods . We investigated by immunohistochemistry, in UIP and COP tissue samples, the expression of most relevant markers of the molecular interplay involving RAGE, oxidant/antioxidant balance regulation, tissue nitrosylation, and mediators of EMT. Results . In both UIP and COP, the degree of RAGE expression was similarly high, while SODs and i-NOS, diffusely present in COP endoalveolar plugs, were almost absent in UIP fibroblast foci. A lower degree of tissue nitrosilation was observed in UIP than in COP. Conclusions . Fibroblast lesions of UIP and of COP share a similar degree of activation of RAGE, while antioxidant enzyme expression markedly reduced in UIP.